2021
DOI: 10.1186/s41747-021-00204-6
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolisation in patients with hepatocellular carcinoma: low-dose doxorubicin reduces post-embolisation syndrome without affecting survival—prospective interventional study

Abstract: Background No chemotherapeutic agents have been standardised for transarterial chemoembolisation (TACE). In particular, doxorubicin has no defined optimal dosage in TACE procedures. We compared low versus currently used dose of doxorubicin for TACE in patients with hepatocellular carcinoma (HCC) in terms of severity of post-embolisation syndrome (PES) and overall survival (OS). Methods From October 2014 to March 2018, we enrolled patients with prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Up to date, there is no established optimal dosage for doxorubicin in TACE procedures (19). In this study, it was found that a higher dose of doxorubicin was significantly associated with the occurrence of PES, suggesting that medication management could be a key area for reducing PES risk.…”
Section: Discussion Discussionmentioning
confidence: 69%
“…Up to date, there is no established optimal dosage for doxorubicin in TACE procedures (19). In this study, it was found that a higher dose of doxorubicin was significantly associated with the occurrence of PES, suggesting that medication management could be a key area for reducing PES risk.…”
Section: Discussion Discussionmentioning
confidence: 69%
“…This term includes symptoms, such as pain, nausea, vomiting and fever, that occur after the treatment. The incidence of these symptoms ranges from 20% to 80% 25,26 . According to the available data, the type of embolic agent (permanent or temporary 25 ), the dose of the chemotherapeutic agent and the size and numbers of the liver tumours play a role 26 .…”
Section: Postembolization Syndromementioning
confidence: 99%
“…The incidence of these symptoms ranges from 20% to 80%. 25,26 According to the available data, the type of embolic agent (permanent or temporary 25 ), the dose of the chemotherapeutic agent and the size and numbers of the liver tumours play a role. 26 However, there are no controlled studies on this complex topic.…”
Section: P Os Te Mbo Liz Ation Syndromementioning
confidence: 99%
“…D-TACE is the use of drug-eluting microspheres loaded with chemotherapeutic drugs for tumor embolization, which has been widely used in clinic in recent years. The most common side effect after D-TACE is post-embolization syndrome, [7,8] including All participants information, images and inspection results are agreed to be published and have obtained informed consent. The details, images will be freely available on the internet and may be seen by the general public.…”
Section: Introductionmentioning
confidence: 99%